Early heparin therapy reduces mortality risk in hyperthermic sepsis patients: A retrospective analysis of the MIMIC-Ⅳ database - Xu Haoran; Li Yiming; Peng Zhiyong (生物医学转化)
Objective To investigate the association between body temperature and coagulation function in septic patients, and to evaluate the effect of early heparin therapy on the prognosis of septic patients across varying temperature states. Methods Data were extracted using structured query language(SQL) from the MIMIC-Ⅳ database, and clinical characteristics of patients were analyzed with R(4.3.2). Differences in coagulation function across various temperature states and the effect of early heparin therapy on prognosis were examined. Results (1) A non-linear relationship was identified between body temperature and mortality in septic patients; (2) Patients in the hypothermic cohort(≤ 37.0℃) demonstrated prolonged prothrombin time(PT) and partial thromboplastin time (PTT); (3) Early heparin therapy increased mortality risk in the hypothermic cohort(≤ 37.0℃) but decreased mortality risk in the hyperthermic cohort(＞ 38.5℃). Conclusion A significant association exists between body temperature and coagulation function in septic patients. An optimal body temperature range(37.0~38.5°C), along with shorter PT and PTT, may be associated with better prognosis. Early heparin therapy can reduce the mortality risk in hyperthermic patients (＞38.5°C).